Genetic Cardiomyopathies A Clinical Approach - Sinagra, Gianfranco.; Mestroni, Luisa.; Camerini, Fulvio. (Springer Milan : Imprint: Springer, 2013)
In the last decade, genetics has been emerging as a primary issue in the diagnosis and management of cardiomyopathies. This book is intended to be a state-of-the-art monograph on these diseases, describing their genetic causes, defining the molecular basis and presenting extensive descriptions of genotypephenotype correlations. Other chapters are focused on the role of clinical observation, on ECG and echocardiography. With its highlight on the most recent discoveries in the field of molecular genetics as well as on the correct clinical approach to patients with heart muscle disease, the book is aimed at physicians and clinical cardiologists with a particular interest in myocardial diseases and in their genetic causes.